Protease activity as a marker of Bacillus spore germination and its utility for spore eradication - Tehri, Nimisha; Thakur, Geetika; Singh, Namita Ashish; yadav, Avinash; Kumar, Naresh; HV, Raghu (Indian Journal of Dairy Science, 2022)
Bacterial spores are of major concern to the food and dairy industry due to their ability to survive during food processing and their potential to germinate, thereby decreasing its safety and shelf-life. The execution of spore germination preceding to elimination step is a potential strategy to eradicate the various spores. Biomarkers of spore germination possess a high level of specificity for differentiation in dormant and germinating spores. In present study, the activity of protease released during germinant induced germination of Bacillus megaterium spores was determined in terms of casein hydrolysis using petriplate and microtitre plate assay. The expression of protease was observed positive for germinating spores as determined by appearance of clear zone (12 mm) due to casein hydrolysis on skim milk agar and enhanced fluorescence [3.63-97.98 (Ã—103) FU] upon cleavage of FITC-labeled casein. Findings on protease expression by germinating spores were validated with refractility loss observed by phase contrast microscopy. The outcome demonstrates the scope of caseinolytic principle for determination of germination mediated protease in order to explore the significant aptitude of protease as keynote marker of spore germination. The developed germination method can be helpful for reducing contamination of Bacillus spores in food and dairy industry subsequently minimizing the occurrence of food poisoning outbreaks